2004
DOI: 10.1097/01.aog.0000127037.12652.76
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Outcome Among Singleton Infants Conceived Through Assisted Reproductive Technology in the United States

Abstract: III

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
74
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(77 citation statements)
references
References 23 publications
(24 reference statements)
1
74
1
1
Order By: Relevance
“…Pregnancies after IVF treatment have been shown to be complicated by higher incidence of fetal and maternal complications, such as small for gestational age, preterm delivery, preeclampsia, placenta praevia, and placental abruption, compared with spontaneous conceptions (12,13). Maternal and pregnancy characteristics could account for these complications to a greater extent than IVF treatment per se.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancies after IVF treatment have been shown to be complicated by higher incidence of fetal and maternal complications, such as small for gestational age, preterm delivery, preeclampsia, placenta praevia, and placental abruption, compared with spontaneous conceptions (12,13). Maternal and pregnancy characteristics could account for these complications to a greater extent than IVF treatment per se.…”
Section: Discussionmentioning
confidence: 99%
“…Such outcomes include, but are not limited to, preeclampsia and pregnancy-induced hypertension, placenta previa, placental abruption, preterm labor, small-forgestational-age (SGA) infants, intrauterine growth restriction, and preterm delivery. [4][5][6][7][8][9][10] The precise cause of the difference in obstetric outcomes between IVF and spontaneous pregnancies is yet unknown, although it has been suggested that aberrant placentation may be an initial pathologic step. Increasing data are establishing IVF placentas to be morphologically different; in a murine model, placentas in the IVF-exposed group were shown to have impaired amino acid and nutrient transport mechanisms.…”
mentioning
confidence: 99%
“…In 2007 142,415 IVF cycles were performed in the United States, accounting for the birth of 57,564 infants (2). Although the majority of children born through fertility treatments are healthy, these treatments have been associated with adverse pregnancy outcomes including but not limited to preeclampsia, placental abruption, placenta previa, preterm labor and delivery, and low birth weight (3)(4)(5)(6)(7)(8)(9). Although several studies have reported increased risks, it does not appear to be related to an increased risk of cytogenetic abnormalities in pregnancies conceived by assisted reproduction technologies (ART) (10,11).…”
mentioning
confidence: 99%
“…Schieve et al (7) estimated that the rate of low birth weight singletons conceived with assisted reproduction is 2.6 times higher than the general population. Most studies on singleton pregnancies obtained by IVF have revealed relative risks of preterm labor ranging from 1.6 to 2.5, with absolute risk increases of 3.8 to 7.8% (3,(25)(26)(27)(28).…”
mentioning
confidence: 99%